Improved Blasting Control and Quantity Calculations Using Reflectorless Laser Systems - Cam Thomas (International Society of Explosives Engineers, 2003)
The initial application for reflectorless laser technology was for profiling rock faces to determine front row burden and improve flyrock control and airblast. Over the past fifteen years a number of laser systems have been developed for general ground modeling purposes and GPS offsets, but these advances have yet to gain common acceptance in construction, mining and quarry blasting. This paper will outline a number of applications for reflectorless laser technology, including the latest method for rock face profiling, mapping, and 3-D modeling to calculate available and excavated rock volumes. Drilling deviation measurements will be presented in conjunction with rock face profiling to demonstrate how this information can be used to improve blast results. In complicated excavations, the actual quantity of rock excavated for payment purposes and the amount of overbreak can be very controversial. Procedures to calculate these volumes using laser technology will be outlined and comparisons will be made between these results and traditional techniques.